COMPARISONS OF PRODUCTION COSTS OF JAPONICA RICE BETWEEN CHINA AND KOREA - Pan Weiguang (Zhejiang University, 2005)
In order to compare the comparative advantage of japonica between China and Korea, the study analyzes the production cost. After comparing the cost and its structure, it is found that the production of Japonica in China has more comparative advantage obviously. But the increasing rate is much higher than that of Korea in recent 10 years. In the long term, the gap between two countries will become smaller, while the inferior advantage of Korea can't be changed during short-mid term. Some measures should be adopted to develop the competitiveness of japonica in Korea, such as, adjusting agricultural structure, enlarging the land scale and making quality differentiation.
Keywords: Japonica Production cost Comparison; Japonica Production cost Comparison